2011
DOI: 10.5777/paet.v4.n1.11
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica dos nutrientes do solo em áreas destinadas à produção de milho para forragem

Abstract: ResumoO milho, quando cultivado para produção de forragens, requer cuidados especiais com relação ao manejo do solo. Com a colheita total da parte aérea, grandes quantidades de nutrientes são removidas, podendo causar prejuízos ao balanço de nutrientes e rápido empobrecimento do solo, tendo como consequência a queda de produtividade e baixa qualidade da silagem em cultivos posteriores. O objetivo deste trabalho é esclarecer aspectos sobre a dinâmica de extração e exportação de nutrientes do solo pela cultura d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
1
2
0
7
Order By: Relevance
“…The results corroborate the observations of Ueno et al (2011), who reported that maximum K absorption by corn plants occurs in the period of 30 to 40 days after germination, even if its absorption exceeds the absorption of N and P, which suggests higher K requirement in the initial development stage of corn plants. The decrease in K contents in the stalks, between 40 and 52 DAE, is probably related to the redistribution of the nutrients used for the development of flower organs.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results corroborate the observations of Ueno et al (2011), who reported that maximum K absorption by corn plants occurs in the period of 30 to 40 days after germination, even if its absorption exceeds the absorption of N and P, which suggests higher K requirement in the initial development stage of corn plants. The decrease in K contents in the stalks, between 40 and 52 DAE, is probably related to the redistribution of the nutrients used for the development of flower organs.…”
Section: Resultssupporting
confidence: 82%
“…Crop nutritional requirements are determined by the amount of nutrients that plants are able to extract from the soil (Ueno et al, 2011). This extraction depends on the obtained yield and the accumulation of nutrients in the grains and in other plant parts.…”
Section: Introductionmentioning
confidence: 99%
“…According to IPA (2008), contents above 0.2 cmol c dm -3 of exchangeable potassium in soil are considered high or adequate, evidencing that cassava wastewater garanteed an adequate contribuition of potassium only at 20 and at 40 DAG for doses above 20 and 40 m 3 ha -1 , demonstrating that in this period, cassava wastewater ensured an adequate potassium supply. At 52 DAG, the potassium contained in residue was not sufficient to mantain the exchangeable potassium of soil in adequate levels, even when higher doses of cassava wastewater were used, showing that, possibly, the absorption of this nutrient by maize plants was higher, once the maximum absorption of K by maize plants occurs in the period from 30 to 40 days after germination, overcoming the absorpion of N and P in this period, as reported by UENO et al (2011). CARDOSO et al (2009) obtained similar results to the ones in this study, when using cassava wastewater in maize crop, statiing that there was a potassium increment in a dystrophic Quartzarenic Neosol (Entisol) comparable to an area where mineral fertilization was conducted.…”
Section: Resultsmentioning
confidence: 71%
“…Porém, de acordo com YAMADA & ROBRTS (2005), no milho destinado à produção de silagem, deve-se tomar cuidado na recomendação do nutriente pelo corte e retirada de todo material. Estudando a dinâmica de nutrientes no solo em áreas para produção de milho silagem, UENO et al (2011) observaram uma exportação média de 76kg ha -1 a mais de K, quando comparada ao milho para produção de grãos. Logo, a utilização da vinhaça como fonte de K, além de representar uma importante alternativa de descarte, pode reduzir a dependência de insumos externos e, consequentemente, redução do custo de produção.…”
Section: A Vinhaça Resíduo Do Processo De Destilação Do áLcool é Ricunclassified